2012 China Enterprise Survey : Country Highlights - World Bank (Washington, DC, 2014)
The World Bank interviewed a representative sample of the private sector composed of 2700 business establishments from November 2011 through March 2013 across 25 of the largest cities in China. The Enterprise Survey covers several topics of the business environment as well as performance measures for each firm. Below are the main highlights from the survey.